1986
DOI: 10.1902/jop.1986.57.12.727
|View full text |Cite
|
Sign up to set email alerts
|

Guided Tissue Regeneration: An Experimental Procedure in Beagle Dogs

Abstract: This preliminary study examined the healing following an experimental procedure designed to facilitate coronal migration of progenitor cells from the periodontal ligament circumferentially on roots of premolar teeth in beagle dogs. Mucoperiosteal flaps were reflected on the buccal and lingual aspects of premolars in six beagle dogs with periodontal disease. Following root preparation, pieces of orthodontic wire were placed interproximally on the crowns to bridge the spaces between teeth. Biobrane, a synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
2
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 21 publications
1
49
2
3
Order By: Relevance
“…56 The so-called "long junctional epithelium" is the mode of attachment even in periodontal tissues where the pocket depths appear to reduce significantly and clinical attachment levels show substantial gains. Such an epithelial attachment is also seen between new bone and the root surface.…”
Section: Regeneration Of Connective Tissue Attachment To Previousmentioning
confidence: 99%
See 1 more Smart Citation
“…56 The so-called "long junctional epithelium" is the mode of attachment even in periodontal tissues where the pocket depths appear to reduce significantly and clinical attachment levels show substantial gains. Such an epithelial attachment is also seen between new bone and the root surface.…”
Section: Regeneration Of Connective Tissue Attachment To Previousmentioning
confidence: 99%
“…39 56 -76 ' 83 The extent of new attachment formation reported varies and it appears that predictability is yet to be established. 56 The reasons for variations in the healing pattern can be attributed to our lack of understanding of the healing mechanisms at the cellular and molecular levels. For example, it has not been proven that placement of physical barriers in wounds actually favors the coronal migration of cells originating from the remaining periodontal ligament.…”
Section: Regeneration Of Connective Tissue Attachment To Previousmentioning
confidence: 99%
“…There are many studies reported in literature which discusses periodontal regeneration of teeth in experimental animal subjects with periodontal pathology by using Guided tissue regeneration (GTR) membranes [49][50][51][52]. Further, Nayman et al was successful in regenerating periodontium like tissues in periodontolly involved human tooth by using GTR membrane [53].…”
Section: Approaches For Periodontal Regenerationmentioning
confidence: 99%
“…For example, dentin production was shown to be induced by calcium hydroxide in pulp-capping procedures in the 1980s [14] , although the underlying mechanisms remain elusive. Guided tissue regeneration was successfully used to regenerate periodontal tissues and had become a successful and widely available clinical therapy [15] . The emergence of whole-tooth tissue engineering stemmed from the demand for biologically based dental tissue and wholetooth replacements and was made possible by the marriage of biological, developmental and material sciences [13] .…”
Section: Dental Stem Cells and Tooth Tissue Engineeringmentioning
confidence: 99%